Six Main Priorities for Better Driving License Services: Enam Prioritas Utama untuk Peningkatan Layanan Surat Izin Mengemudi - Husniyyah Husniyyah; Sumiati Sumiati (Universitas Muhammadiyah Sidoarjo, 2025)
(General Background) Public service quality is a fundamental aspect of building public trust in government institutions, particularly in administrative services such as the issuance of driving licenses (SIM) managed by SATPAS. (Specific Background) However, despite the government’s efforts, the public often perceives the service as inefficient, with long queues, inconsistent procedures, and unprofessional staff attitudes. (Knowledge Gap) Previous studies have not specifically identified which service attributes most influence customer satisfaction and how these can be systematically improved. (Aims) This study aims to evaluate the quality of SATPAS services using the Importance Performance Analysis (IPA) method and to formulate improvement strategies through the 5W+1H approach. (Results) The findings show an average satisfaction score of 3.29 and a conformity level of 83%, indicating a service quality gap. Six attributes were identified as main improvement priorities: service punctuality, speed, staff readiness, information clarity, cost transparency, and staff politeness. (Novelty) The integration of IPA and 5W+1H provides a structured and practical framework for prioritizing and implementing service improvements. (Implications) The proposed model can be applied in other public institutions to enhance accountability, efficiency, and citizen satisfaction in public service delivery. Highlights: Identifies six key priorities for improving SATPAS service quality. Combines IPA and 5W+1H methods for targeted service enhancement. Provides a practical framework to boost efficiency and public trust. Keywords: Service Quality, Importance Performance Analysis, 5W+1H, Public Service, Customer Satisfaction